2015
DOI: 10.1515/pjs-2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Risk Factors Of Positive Peritoneal Cytology In Patients Treated For Gastric Cancer – Preliminary Report*

Abstract: Presence of free gastric cancer cells in the peritoneal cavity of patients who underwent surgical treatment for gastric cancer is a negative prognostic factor and caused rapid disease recurrence, manifested as peritoneal metastases. Positive peritoneal cytology despite lack of visible peritoneal metastases was regarded as M1 class in the TNM classification (7 th edition) in 2010. the aim of the study was to analyze factors associated with positive peritoneal cytology and identify groups of patients in whom dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The majority of the included studies used T4 as a criterion, and T4's relevance with PC is also consistent with the "seed and soil" hypothesis, which states that more free cancer cells exfoliated from the tumor penetrating serosa could lead to PC (34). However, if all three studies with CY1 only were included in the analysis, then OR (95% CI) was 1.65 (0.79-3.44), which means that there is no statistical difference (19,21,22). Yoshida et al found the occurrence of CY1 or P1 in five of the 1,509 patients with early gastric cancer, and pathological analysis revealed that the primary tumor invaded the submucosa and metastasized to the regional lymph nodes through the lymph vessels; they speculated that tumor cells may metastasize to the peritoneal cavity through the lymphatic system rather than by breaking through the plasma (35).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The majority of the included studies used T4 as a criterion, and T4's relevance with PC is also consistent with the "seed and soil" hypothesis, which states that more free cancer cells exfoliated from the tumor penetrating serosa could lead to PC (34). However, if all three studies with CY1 only were included in the analysis, then OR (95% CI) was 1.65 (0.79-3.44), which means that there is no statistical difference (19,21,22). Yoshida et al found the occurrence of CY1 or P1 in five of the 1,509 patients with early gastric cancer, and pathological analysis revealed that the primary tumor invaded the submucosa and metastasized to the regional lymph nodes through the lymph vessels; they speculated that tumor cells may metastasize to the peritoneal cavity through the lymphatic system rather than by breaking through the plasma (35).…”
Section: Discussionmentioning
confidence: 55%
“…Five studies, with 1,427 patients, from 2015 to 2020 were included ( 15 , 16 , 19 , 24 , 30 ). The sample size of the studies changed from 51 to 804.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable results were identified (risk difference: 0.32; 95% CI: 0.19–0.44; n=600 patients; I 2 =55%; p <0.00001) when analyzing studies that evaluated oncologic stages according to the UICC/AJCC system 7 th edition 26,31,38,59,97.…”
Section: Resultsmentioning
confidence: 98%
“…In Poland, positive cytology is detected in 24% of all patients initially scheduled for radical surgery [40]. Factors that are predictive for positive cytology of peritoneal fluid include: stage T3/4, lymph node involvement, grade score G3, infiltration by the tumour of the entire stomach and indications of a diffuse type of GC by Laurén classification.…”
Section: Preoperative Laparoscopic Pci Evaluationmentioning
confidence: 99%